KONTRA-RADIKALISASI AGAMA BERBASIS AJARAN TASAWUF DI INSTITUT AGAMA ISLAM NEGERI PEKALONGAN - M. Aba Yazid; Maulida Ayu Pangesti (Institut Agama Islam Al-Hikmah Tuban, 2022)
This study aims to explore the strategy of counter-radicalization of religion among IAIN Pekalongan students. Qualitative research in the form of field research is descriptive-analytical. Data collection through interviews and documentation. Students who became informants, namely students of the Faculty of Tarbiyah and Teacher Training and the Faculty of Usuludin Adab, and Da'wah. Secondary data in the form of a variety of scientific research that is correlated with the core of the discussion. Meanwhile, the data analysis technique is through data reduction, data presentation, and data verification. The results of the study stated that the strategy of counter-radicalization of religion among IAIN Pekalongan students was through the internalization of Sufism teachings with two methods. First, the ta'lim method, namely through teaching various Sufism teachings in learning Sufism courses in the classroom, including the teachings of zuhud, tawasuth, and rahmatan lil alamin. Second, the ta'dib method, namely the habit of reading Asmaul Husna on student activities, such as starting learning in class, completing fardhu prayers in congregation, and at the opening of every religious activity. The strategy of counter-radicalization of religion in practice can lead to the formation of moderate religious understanding and social attitudes of students, neither extreme left nor right. The theoretical implication of this research shows that the application of Sufism teachings is compatible in shaping the character of moderate Islamic understanding and religious attitudes, so that it can become the basis of values as well as the paradigm of counter-radicalization of religion The limitation of this research is that it has not examined the role of the local government or local community leaders in the succession of the religious counter-deradicalization program at IAIN Pekalongan